MINAT BELAJAR PENDIDIKAN AGAMA ISLAM SISWA KELAS X DI SMAN 1 PALUPUH NAGARI PASIA LAWEH KECAMATAN PALUPUH KABUPATEN AGAM - Khalisa Dean Airiza; Alimir; Supriadi; Jasmienti (Universitas Pahlawan Tuanku Tambusai, 2022)
The background of this research is that during the learning process, there are still students who show an unhappy face, some students are less interested in learning PAI, and also the lack of concentration of some students on PAI subjects. It can be seen from some students who do things other than teaching and learning activities. Besides that, there are also some students who have not been able to understand the material presented by the teacher in class, there are still students who are less active in the learning process, and some students are also affected by the surrounding environment. This research uses a qualitative descriptive research type. This research is located at SMAN 1 Palupuh. The key informants in this study were 10 students of class X IPS 3 and the supporting informants were PAI teachers and homeroom teachers of class X IPS 3 students. To collect data, the authors conducted interviews, observations, and documentation. After the data has been collected, the authors analyze the data. Furthermore, to ensure the validity of the data, the authors triangulate the data. Based on the results of the study, the authors can draw conclusions, that in the interest in learning PAI students in class X IPS 3, there are several causes for the low interest of students in learning PAI, as follows: Internal factors. Namely, the physical aspect, the psychological aspect which includes: lack of attention, poor student responses, the ability of students to learn PAI, and lack of student motivation in learning PAI. And external factors. First, the family environment: lack of support from parents, lack of parental attention to the student's learning process, and a home atmosphere that does not support students to study well. The second is the school environment: the way the teacher teaches, the condition of the classroom is not conducive, and the methods used by the teacher. The third, the community environment: the influence of friends, the influence of gadgets, unfavorable environmental conditions, and busy with activities in the community. Keyword: Interest in Learning, PAI Learning